Physicochemical Characteristics and Consumer Acceptance of Bagged Indonesian Green Tea (Camellia sinensis) Formulated with Cinnamon Bark (Cinnamomum burmannii) and Lemon (Citrus limon) Peel - Kirana, Adinda; Sunarharum, Wenny Bekti (Graduate School, Universitas Brawijaya, 2020)
Green tea is a popular functional beverage mostly due to its high antioxidant activity. However, based on preliminary study, the taste such as its bitterness and flavour were somehow disliked by Indonesian consumers, and therefore formulation with other materials such as the addition of cinnamon and lemon peel may bring an advantage.This research was aimed to study the effect of formulation of bagged Indonesian green tea with cinnamon and lemon peel to the physicochemical characteristics of the tea and its consumer acceptance. Evaluation on the effect of different steeping time while brewing those tea formulas was also reported. The formula being investigated was F1, F2, and F3 with green tea: cinnamon: lemon peel at the ratio of 70:15:15, 70:12:18, and 70:9:21, respectively.Tea brewing was performed at 100Â°C, followed by a steeping time (L) at 1, 3, and 5 minutes. The results indicated that the addition of more cinnamon and longer steeping time had increased total phenol and antioxidant activity of the brewed tea. Based on the consumer acceptance test, the formula ofgreen tea: cinnamon:lemon peel at 70:15:15 along with 3 minutes steeping time, was generally scored highest for degree of liking but the ratio of 70:12:18 was the most accepted or preferred for aroma.The best treatment was achieved on the ratio of green tea:cinnamon:lemon peel = 70:12:18, under 5 minutes steeping time. The best treatment provided a pH of 5.13, lightness (L*) at 44.93, redness(a*) at -2.50, yellowness (b*) at 16.93, total phenol of 59.82 mgGAE.g-1, and IC50 of 59.39 ppm.